Towards seamless pedestrian navigation - Peltola, Pekka (2018)
The best methods for processing a positioning solution vary between the positioning technologies. The main methods are examined and the best are chosen and used in the final implementation. The path-loss modelling is the faster method when using BLE. It is slightly more advantageous, although slightly less accurate, when compared with the very laborious Fingerprinting alternative. For an UWB system, the accurate timing method is the better option over the signal strength measures.